Antiquity revisited: Challenges and opportunities in the creation of the new Greek history curriculum. Issue 2 (17th October 2019) - Kasvikis, Kostas; Kouseri, Georgia
This paper presents and discusses the rationale behind the curriculum covering ancient Greek history, a topic that is taught twice during the course of Greek compulsory education (covering 6–15 year olds). The undertaking to develop a new history curriculum set the framework for a reconsideration of themes and approaches to the teaching of antiquity, based on changes to the scope, aims, teaching topics, methodological approaches and assessments introduced. The approved new history curriculum attempts to elevate the status of prehistory relative to other historical periods, so as to strike a balance between local, national and global history, highlighting the common origin and evolution of modern humans. It introduces archaeology, material culture and museums as structural tools for research into and understanding of antiquity by students. It also focuses on social and cultural history, and reassesses dominant historiographical views of the ancient world. Additionally, a methodological framework that encourages students to create their own accounts and interpretations of the ancient past is recommended, by proposing activities that support historical enquiry and the development of key historical concepts.